Severe acute pulmonary embolism in pregnancy - Bhaskar Narayan (Clinical Medicine)
Pulmonary embolism (PE) is a significant cause of morbidity and mortality in pregnancy and the puerperium. In severe cases, it causes haemodynamic instability and can lead to cardiac arrest due to obstructive shock. Patients with acute PE can be risk stratified to guide their monitoring and treatment; this article focuses on intermediate- and high-risk PE. The criteria for defining high-risk PE can be used unmodified in pregnancy. Diagnostic imaging should not be delayed due to pregnancy. Low-molecular-weight heparin (LMWH) and unfractionated heparin (UFH) can be used during pregnancy and breastfeeding, and systemic thrombolysis can be used in obstetric patients, but there are significant bleeding risks and it should be reserved for high-risk PE with hypotension and shock. Although pregnancy and the puerperium are risk factors for PE, it is important to avoid early diagnostic closure, and to consider other causes for the patient’s presentation.